Identification of the Regulator of G-Protein Signaling Protein Responsive to Plant Hormones and Abiotic Stresses in Brassica napus - Yun CHEN; Xia ZHU; Xiao-bin ZHU; Yi-fan YU; Hui-min GE; Yong GAO; Jian-sheng LIANG (Journal of Integrative Agriculture)
Regulator of G protein signaling proteins (RGS) accelerate the rate of GTP hydrolysis by Gα proteins, thus acting as negative regulators of G-protein signaling. Studies on Arabidopsis and soybean have proven that RGS proteins are physiologically important in plants and contribute to the signaling pathways regulated by different stimuli. Brassica napus is an important agriculturally relevant plant, the wildly planted oilseed rape in the world, which possesses an identified Gα, Gβ and Gγ subunits. In the present study, we identified and characterized a Brassica napus RGS gene, BnRGS1, which contained an open reading frame of 1380 bp encoding a putative 52.6 kDa polypeptide of 459 amino acids, within seven putative transmembrane domains in the N-terminal and RGS box in the C-terminal. BnRGS1 is located on the membrane in onion epidermal cells and tobacco leaves, and interacts with BnGA1 in the mating-based split-ubiquitin system. The expression levels of BnRGS1 were quite different in different tissues and developmental stages, and induced by abscisic acid (ABA) and indole-3-acetic acid (IAA). The effects of gibberellin (GA3) and brassinolide (BR) on the expression of BnRGS1 were irregular under the concentrations tested. Moreover, the transcript level of BnRGS1 was also induced by polyethylene glycol (PEG), whereas remained little changed by 200 mmol L−1 NaCl. These results suggested that the BnRGS1 may be involved in B. napus response to plant hormone signaling and abiotic stresses.